Critical infrastructure vulnerability: a research note on adaptation to climate change in the Nordic countries. Issue 1 (2nd January 2021) - Silvast, Antti; Kongsager, Rico; Lehtonen, Turo-Kimmo; Lundgren, Minna; Virtanen, Mikko
ABSTRACT: This research note reviews recent literature on the vulnerability of critical infrastructures caused by climate change with a focus on the Nordic countries. We integrate literature from three research areas: the role of critical infrastructures in the functioning of society, infrastructural vulnerabilities, and the long-term impacts of climate change. Focusing on climate change adaptation in the Nordic countries as a pivotal case, we discuss the mutually constitutive interrelationships between these three areas. The studies reviewed bring together social science and humanities research on infrastructure systems, their vulnerabilities, and climate change. By highlighting interdisciplinary perspectives on infrastructures, climate change, and societal security, this research note discusses a Nordic model of infrastructure provision and links the Nordic debate to a burgeoning European discussion on the role of the social sciences and humanities in addressing societal challenges related to climate change and the role of infrastructures in providing welfare.